Impacto da transmissão cruzada de micro-organismos epidemiologicamente importantes em uma UTI neonatal - Alves, Priscila Guerino Vilela (2023)
Introduction: Bloodstream infection caused by Candida spp. it is recognized as one of the main causes of morbidity and mortality in newborns. Studies carried out around the world show an association between infections acquired in the hospital environment and the practice of washing hands and inanimate reservoirs. This fact causes the environmental transmission of virulent microorganisms and the concern for the safety of the newborn becomes even greater. Therefore, epidemiological assessment of infections in the NICU is necessary. Objective: to analyze Candida species isolated from the hands of healthcare professionals, before and after cleaning with 70% ethyl alcohol-based gel, from the environment and from bloodstream infections in the NICU, and evaluate virulence factors, biofilm production and genetic similarity. Methodology: Isolates were identified using MALDI-TOF. Antifungal susceptibility tests were performed in accordance with documents from the Clinical and Laboratory Standard Institute. The isolates were studied to produce extracellular hydrolytic enzymes (hemolysin, Dnase, proteinase and phospholipase) through phenotypic tests (egg yolk agar, bovine albumin agar, 7% sheep blood agar and Dnase agar); biofilm formation and metabolic activity were assessed using crystal violet and XTT staining, respectively. Genetic similarity was performed using randomly amplified polymorphic DNA (RAPD-PCR) methodology. Epidemiological surveillance was carried out through the “National Healthcare Safety Network” system. Results: C. parapsilosis complex was the most common species. Three isolates obtained from the hands of professionals were resistant to amphotericin B, one was resistant to micafungin and five were resistant to fluconazole. One environmental isolate showed dose-dependent susceptibility to fluconazole. Two bloodstream isolates were resistant, one to fluconazole and the other to micafungin. All isolates were capable of producing at least one of the investigated virulence factors. A molecular analysis by RAPDPCR revealed identical strains that were in the hands of different professionals, and also revealed a cluster with five highly similar strains (Sj > 80%) of C. parapsilosis stricto sensu, four from the environment and one from the bloodstream. Conclusions: Candida species were isolated from hands and the environment even after hygiene and disinfection. The environment may have been a source of infection, as isolates from the environment and infections contain similar genetics. Some hand isolates had high genetic similarity and were in different healthcare professionals and groups, highlighting the importance of hand hygiene to minimize the risk of cross-contamination in NICUs, and highlighting the importance of more rigorous basic measures to control hospital acquired infections.